The Effect of Competency and Motivation on Employee Performance with Service Leadership as A Moderating Variable: Study at The Semarang Productivity Vocational Training Center - Adi Purnomo Adi Purnomo; Tristiana Rijanti (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze the influence of competence and motivation on employee performance, while also examining the moderating role of servant leadership. Competence and motivation are considered key drivers of improved performance; however, their effectiveness may vary depending on the leader-ship style adopted within the organization. This research employs a quantitative method using a survey approach targeting employees at BBPVP Semarang. Data were collected through questionnaires and analyzed using multiple linear regression techniques. The findings reveal that competence has a positive and significant impact on employee performance, whereas motivation does not show a direct effect. Furthermore, servant leadership was found to weaken the relationship between competence and per-formance but strengthen the link between motivation and performance. This suggests that the more servant leadership is applied, the stronger the influence of motivation on employee performance. These findings offer practical implications for organizations to focus on competence development, enhancing employee motivation, and adopting a service-oriented leadership style to foster optimal performance.